Predictors of Restenosis Following Carotid Angioplasty and Stenting. Issue 8 (August 2016) - Zapata-Arriaza, Elena; Moniche, Francisco; González, Alejandro; Bustamante, Alejandro; Escudero-Martínez, Irene; De la Torre Laviana, Francisco Javier; Prieto, María; Mancha, Fernando; Montaner, Joan
Abstract : Background and Purpose—: Restenosis after carotid angioplasty (with or without stent) is associated with increased rate of stroke and death. Our aim was to determine risk and predictive factors related to carotid restenosis post carotid angioplasty and its association to recurrent cerebrovascular events. Methods—: All consecutive patients with carotid stenosis treated with angioplasty (n=1060) in a single University Hospital were included (from 2002 to 2013). Follow-up was done prospectively evaluating restenosis, ipsilateral stroke, or death. Restenosis was defined as a narrowing of ≥70% of a previously treated vessel evaluated by ultrasonography. Results—: Of the 1060 patients treated, 9.2% (97) of patients experienced restenosis during follow up (median 12 [9–32] months). Occurrence of restenosis was associated with ipsilateral stroke during follow-up ( P =0.049). After Cox regression analysis, hypertension (hazard ratio, 6.2 [1.9–19.9]; P =0.002), impaired vasoreactivity (hazard ratio, 1.7 [1.09–2.8]; P =0.019), and angioplasty without stent (hazard ratio, 2.9 [1.2–6.8]; P =0.012) were independent risk predictors of >70% restenosis. Conclusions—: Carotid restenosis after carotid angioplasty is associated with ipsilateral stroke occurrence. In our sample, hypertension, angioplasty without stent, and impaired vasoreactivity identify patients at high risk of restenosis and could help to select patients for follow-up ultrasonography imaging. Abstract : Supplemental Digital Content is available in the text.